História da ciência x aprendizagem: algumas semalhanças detectadas a partir de um estudo psicogenético sobre las idéias que evoluem para a noção de campo de força - Nardi, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
In this article, based upon a psychogenetic study on the ideas which evolve to the concept of field of force, we show some students' conceptions which seem to be similar to others found in the History of Science. We analyse aspects which could contribute to the construction of the teaching of this concept.